DETERMINATION FACTORS OF BUYING DECISION AT THE INDONESIAN CIGARETTE INDUSTRY - JUN DITA PANGESTU; GINANJAR RAHMAWAN (INTERNATIONAL JOURNAL OF MULTI SCIENCE, 2021)
This research aimed to understanding the decision of buying of Djarum Super cigarettes, especially in Surakarta. The decision is influenced by several factors, namely brand image, price and product quality. This research is conducted with a quantitative approach, which is a method used to assess a population and / or a particular sample. The people of Surakarta as the population in this study determined a sample of 50 respondents who filled in patented benchmarks using purposive sampling. The data obtained were then processed statistically using SPSS (Statistical Package for Social Science). The output of processed data explains simultaneously and partially that purchasing decisions are influenced by product quality, brand image and price which have a significant influence. The output of the analysis of the coefficient of determination (adjusted R2) shows that 52.6% of purchasing decisions are influenced by variables of brand image, price and product quality and another 47.4% are influenced by other variables outside the variables studied.